Advances in dispersive solid-phase extraction techniques for analytical quantification of fluoroquinolone antibiotics - Syaleyana Md Shukri, Dyia; Yahaya, Noorfatimah; Miskam, Mazidatulakmam; Yusof, Rizana; Husaini Mohamed, Ahmad; Kamaruzaman, Sazlinda; Nadhirah Mohamad Zain, Nur; Semail, Nadhiratul-Farihin (Elsevier, 2023)
Misuse and incorrect fluoroquinolones (FQs) disposal have led to environmental pollution and trace amounts of FQs contamination in food chains. Consequently, the quest for innovative, simple, and improved techniques of FQs analyte pre-treatment in real samples has focused on micro- and macroscale dispersive solid-phase extraction (DSPE). Recent studies have reported implementing DSPE-based techniques as a sample preparation step to determine FQs in various sample matrices. The present study summarises current FQs detection methods with various chromatographic and DSPE-based combinations. Furthermore, the merits and the analytical figures of DSPE performance when employed for actual samples were discussed. This study also comprehensively evaluated corresponding challenges, opportunities, and the potential of DSPE in detecting trace levels of FQs. The findings demonstrated that the DSPE-based technique provided undeniable advantages for routine sample pre-treatment of FQs and enhanced analytical performance